Sound Velocities and Elastic Moduli of Phases I and V of Silicon at High Pressures. Issue 8 (8th May 2019) - Zhao, Bin; Xu, Feng; Belliard, Laurent; Huang, Haijun; Perrin, Bernard; Djemia, Philippe; Zerr, Andreas
Abstract : Pressure dependences of longitudinal sound velocities, in the two phases Si‐I and Si‐V of silicon having, respectively, cubic‐diamond and primitive‐hexagonal structures, are measured using the technique of picosecond laser ultrasonics adapted to samples compressed in a diamond anvil cell (DAC). For the Si‐I phase, stable at atmospheric pressure, the longitudinal sound velocity along the 〈100〉 direction is obtained in a single crystal up to 9 GPa. In the case of the Si‐V phase, the average sound velocity for an isotropic polycrystalline sample V L(avg) is measured for the first time between 18 and 27 GPa. Above this pressure, preferred orientation of the hexagonal crystallites of Si‐V, with their c ‐axes parallel to the compressional direction in the DAC and to the acoustic pulse propagation direction, is progressively developing thus precluding further V L(avg) measurement. The experimental single crystal elastic constants C 11 ( P ) and C 12 ( P ) of Si‐I, and the shear modulus of polycrystalline Si‐V deduced here are in a very good agreement with our first principles calculations and with the earlier results reported for Si‐I. Abstract : Longitudinal sound velocities of silicon are studied up to 37 GPa. The experimental and theoretical results reveal that the starting single crystal of Si‐I phase transforms after intermediate phase transitions to isotropic polycrystalline Si‐V, the shear modulus of which was measured for the first time to 27 GPa. Above this pressure, an orientational texturing is recognized.